2020
DOI: 10.2147/dddt.s241022
|View full text |Cite
|
Sign up to set email alerts
|

<p>Investigation of the Inhibitory Effect of Simvastatin on the Metabolism of Lidocaine Both in vitro and in vivo</p>

Abstract: Background: Lidocaine has cardiovascular and neurologic toxicity, which is dosedependent. Due to CYP3A4-involved metabolism, lidocaine may be prone to drug-drug interactions. Materials and Methods: Given statins have the possibility of combination with lidocaine in the clinic, we established in vitro models to assess the effect of statins on the metabolism of lidocaine. Further pharmacokinetic alterations of lidocaine and its main metabolite, monoethylglycinexylidide in rats influenced by simvastatin, were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“… Wang et al (2020) ’s PIM estimate of 67.5% is consistent with that reported from recent studies, although those exploring larger patient populations such as Roux-Marson et al (2020) , found relatively lower PIM prevalence estimates. These include Jones et al (2020) ’s estimate of 13% and Roux-Marson et al (2020) ’s case burden of 45.1% among patients with CKD.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“… Wang et al (2020) ’s PIM estimate of 67.5% is consistent with that reported from recent studies, although those exploring larger patient populations such as Roux-Marson et al (2020) , found relatively lower PIM prevalence estimates. These include Jones et al (2020) ’s estimate of 13% and Roux-Marson et al (2020) ’s case burden of 45.1% among patients with CKD.…”
Section: Introductionsupporting
confidence: 88%
“… Wang et al (2020) ’s recent report on the burden and morbidity consequences of potentially inappropriate medications (PIMs) in a select cohort of type 2 diabetic mellitus (T2DM) patients was both instructive and an “inflection point” in the characterization of the clinical phenotype of this rising morbidity. They found an overall prevalence of 67.5% of PIMs amongst a randomly selected cohort of n = 186 T2DM patients, with the odds of having a PIM phenotype rising 4-fold amongst those hospitalized with concomitant polypharmacy ( American Geriatrics Society, 2019 ; Wang et al, 2020 ). This report significantly advances the narrative regarding the evolving relationship between PIMs and polypharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…25 Meanwhile, due to CYP3A4-involvement in lidocaine metabolism, its pharmacokinetic and pharmacodynamic response can be altered when coadministrated with CYP3A4 modulators such as Simvastatin. 26 In the present study, there was no correlation between initial efficacy and baseline data such as age, sex, pain laterality, pain duration, comorbidities, pain distribution, pain characteristics, and history of previous treatment. We find that facial trigger point is an independent predictor for analgesic efficacy of LMP (OR = 0.25, 95% CI = 0.07-0.86, P = 0.03).…”
Section: Discussioncontrasting
confidence: 62%
“…It is important to note that although the risk of systemic absorption of topical products is relatively low, lidocaine may be prone to pharmacodynamic interactions; caution should also be practiced while using lidocaine in patients receiving Class I antiarrhythmic drugs as the toxic effects can be potentially synergistic. 25 Meanwhile, due to CYP3A4-involvement in lidocaine metabolism, its pharmacokinetic and pharmacodynamic response can be altered when coadministrated with CYP3A4 modulators such as Simvastatin. 26 In the present study, there was no correlation between initial efficacy and baseline data such as age, sex, pain laterality, pain duration, comorbidities, pain distribution, pain characteristics, and history of previous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies have shown that both cytochrome P450 3A4 and 1A2 isoenzymes (CYP3A4 and CYP1A2) are important in the metabolism of lidocaine (37). Clinicians should be aware of the potential increase in toxicity of lidocaine when used with the combination of drugs which inhibit CYP1A2 or CYP3A4 enzymes such as statins (CYP3A4 inhibitor), fluvoxamine (CYP1A2 inhibitor) and erythromycin (CYP3A4 inhibitor) (38,39). Despite the ease of use, rapid-onset pain relief and good tolerability, numbness and bitter taste at the application sites were unavoidable, localized irritation was noted in a small number of patients, though reversible.…”
Section: Discussionmentioning
confidence: 99%